Proceedings of the 2021 Conference on Empirical Methods in Natural Language Processing 2021
DOI: 10.18653/v1/2021.emnlp-main.779
|View full text |Cite
|
Sign up to set email alerts
|

PICARD: Parsing Incrementally for Constrained Auto-Regressive Decoding from Language Models

Abstract: Large pre-trained language models for textual data have an unconstrained output space; at each decoding step, they can produce any of 10,000s of sub-word tokens. When fine-tuned to target constrained formal languages like SQL, these models often generate invalid code, rendering it unusable. We propose PICARD 1 , a method for constraining auto-regressive decoders of language models through incremental parsing. PICARD helps to find valid output sequences by rejecting inadmissible tokens at each decoding step. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 12 publications
1
113
0
Order By: Relevance
“…For SQL semantic parsing (Spider, SParC, and CoSQL), a large number of errors is caused by invalid outputs, and the number of invalid outputs gradually decreases with the increase of model size. This phenomenon is also observed by Scholak et al (2021), who further used the PICARD method to improve output validity, largely improving the parsing performance. For s-expression semantic parsing (GrailQA and We-bQSP), invalid predictions take up 30-50% of all incorrect predictions, and increasing the model size does not significantly reduce invalidity.…”
Section: Error Analysissupporting
confidence: 56%
See 1 more Smart Citation
“…For SQL semantic parsing (Spider, SParC, and CoSQL), a large number of errors is caused by invalid outputs, and the number of invalid outputs gradually decreases with the increase of model size. This phenomenon is also observed by Scholak et al (2021), who further used the PICARD method to improve output validity, largely improving the parsing performance. For s-expression semantic parsing (GrailQA and We-bQSP), invalid predictions take up 30-50% of all incorrect predictions, and increasing the model size does not significantly reduce invalidity.…”
Section: Error Analysissupporting
confidence: 56%
“…Some semantic parsing sota models, denoted as + in Table 2, are also T5 with post hoc modification, e.g., constrained decoding (Scholak et al, 2021) or reranking (Ye et al, 2021b). We conclude that T5, with simple modification when necessary, achieves sota on almost all the tasks.…”
Section: Experiments and Results On Individual Tasksmentioning
confidence: 84%
“…This approach achieves 32.57 BLEU on the CoNaLa dataset compared to the same set up without TAE which scores 30.98 BLEU. Scholak et al (2021) propose PICARD a simple and effective decoder-constraint algorithm that works with pretrained encoder-decoder models. Using PICARD with a T5-3B model (Raffel et al, 2019b) achieves state of the art on two SQL generation tasks from NL Spider (Yu et al, 2018) and CoSQL (Yu et al, 2019a).…”
Section: Pretrained Transformer Modelsmentioning
confidence: 99%
“…Others have proposed to use a generative model like BART to augment the dataset by paraphrasing natural language utterances (Xu et al, 2020b). Recently, it has been shown that T5 can be successfully fine-tuned on a large-scale text-to-sql dataset (Shaw et al, 2021;Scholak et al, 2021).…”
Section: Semantic Parsingmentioning
confidence: 99%